Point-of-care ultrasound-guided resuscitation and transport of an extremely premature infant in a pre-hospital setting: a case report - Bi-Ying, Deng; Jin-Feng, Li; Qin, Chen; Ning, Li; Xiao-Guang, He (Frontiers in Pediatrics, 2026)
A male infant born vaginally with clear amniotic fluid at a gestational age of 24 weeks had Apgar scores of 6 at 1 and 5 min and 7 at 10 min and a birth weight of 600 g. After receiving pulmonary surfactant therapy administered through an endotracheal tube at the local hospital, he continued to exhibit severe respiratory distress and hypoxemia; moreover, obtaining peripheral venous access remained difficult despite mechanical ventilation. Consequently, the neonatal transport team from our hospital was called to assist with treatment and transfer. Upon arrival, the transport team used point-of-care critical ultrasound for dynamic assessment and obtained the following findings: (1) the lung ultrasound assessments excluded pneumothorax and helped optimize the ventilator parameters to achieve patient–ventilator synchrony; (2) endotracheal tube placement was confirmed; (3) cranial ultrasound was performed to screen for intracranial hemorrhage; and (4) ultrasound-guided umbilical arterial and venous catheterization was successfully performed to establish vascular access. Under mechanical ventilation support and continuous monitoring, the infant was successfully transported to our neonatal intensive care unit (NICU), requiring no repeat invasive procedures upon admission and maintaining a stable condition throughout transport. This case demonstrates the effectiveness of point-of-care critical ultrasound for real-time guidance during the resuscitation and transport of extremely preterm infants. By enabling multi-system evaluation that included lung, airway, vascular, and cranial assessments, this approach substantially enhanced management efficiency, reduced complications, and offered reliable technical support for the transport of high-risk neonates.